Application of Gold Nanoparticles Synthesized with Malva Nut Gum as Reducing Agent for scFv Conjugates in a Colorimetric Chikungunya Virus Detection - Muhamad Zulchoir Rasyid; Ratna Yulistya Ningrum; Sinta Setyaningrum; Budi Santoso; Muhammad Yusuf; Bachti Alisjahbana; Toto Subroto; Bevi Lidya (Fluida, 2023)
Gold nanoparticles have good surface plasmon properties in the presence of free electrons on their surface. The presence of free electrons on the surface of the plasmon causes gold nanoparticles to be able to bind to various kinds of biomolecules and proteins, including single-chain variable fragments (scFv). In this study, gold nanoparticle conjugates with Chikungunya antiviral scFv have been successfully prepared with the aim of developing a colorimetric method for rapid detection of envelope protein Chikungunya virus (E2 CHIKV). The manufacture of gold nanoparticles was carried out using malva nut gum and trisodium citrate as reducing agents. The results showed the formation of the AuNP-scFv conjugate which was characterized by a shift in the maximum wavelength for gold nanoparticles synthesized using malva nut gum as a reducing agent from 532.89 nm to 536.62 nm. Similarly, for gold nanoparticles synthesized using trisodium citrate as a reducing agent, the maximum wavelength shifted from 528.99 nm to 531.95 nm. The detection result of E2 CHIKV protein using the AuNP-scFv conjugate has not shown a positive result